2017
DOI: 10.3390/inorganics6010004
|View full text |Cite
|
Sign up to set email alerts
|

Pt(IV)/Re(I) Chitosan Conjugates as a Flexible Platform for the Transport of Therapeutic and/or Diagnostic Anticancer Agents

Abstract: New chitosan derivatives modified with (3-carboxypropyl)trimethylammonium chloride (1) and coupled with (OC-6-44)-diammine(4-carboxypropanoato)dichloridoethanolatoplatinum(IV) (2), were synthesized and their preliminary biological evaluation carried out in human tumor cells. Some of these derivatives were also loaded with a chelating ligand (3) that was derived from bis(quinolin-2-ylmethyl)amine to obtain chitosan-based nanoparticles for an EPR-mediated delivery of Pt(IV) prodrugs and Re(I) tricarbonyl complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…After loading a model drug paclitaxel (PTX), the surface of PTX-TCS-GNSs was modified with the anti-EGFR (epidermal growth factor receptor) antibody by using EDC/NHS-catalyzed amidation reaction . Other amidation reagents such as O -1-benzotriazol-1-yl- N , N , N′ , N′ -tetramethyluronium hexafluorophosphate (HBTU)/ N , N -diisopropylethylamine (DIPEA) pairs and ethyl-3-(3-(dimethylamino)­propyl) carbodiimide (EDAC) were also used in the synthesis of acylated CS.…”
Section: Methods For Chemical Synthesis Of Cs Derivativesmentioning
confidence: 99%
“…After loading a model drug paclitaxel (PTX), the surface of PTX-TCS-GNSs was modified with the anti-EGFR (epidermal growth factor receptor) antibody by using EDC/NHS-catalyzed amidation reaction . Other amidation reagents such as O -1-benzotriazol-1-yl- N , N , N′ , N′ -tetramethyluronium hexafluorophosphate (HBTU)/ N , N -diisopropylethylamine (DIPEA) pairs and ethyl-3-(3-(dimethylamino)­propyl) carbodiimide (EDAC) were also used in the synthesis of acylated CS.…”
Section: Methods For Chemical Synthesis Of Cs Derivativesmentioning
confidence: 99%
“…This pH-sensitive prodrug could have a certain potential for cancer therapy along with imaging [69]. Gabano et al suggest that the chitosan nanoparticle conjugated with the chemotherapeutic agent cisplatin and the photosensitizer Re(I) tricarbonyl complex could be used as a theranostic by replacing the fac-[Re(CO)3] + by the congener fac-[99mTc(CO)3] + core [93].…”
Section: Chitosanmentioning
confidence: 99%
“…In recent years, efforts have been made for the development of metallodrugs, a strategy to combine two or more active transition metals in a single platform in order to achieve a synergistic effect of two metals. To date, pioneering studies have been reported to improve the cytotoxicity of Pt­(IV) prodrugs by combining with other metals which include Cu­(II), Fe­(II), , Ru­(II), ,, Re­(I), Gd­(III), , Au­(I), etc. For instance, Zhu and co-workers have reported heterodinuclear Pt­(IV)-Ru­(II) anticancer prodrugs to combat both drug resistance and cancer metastasis. , Gasser and co-workers have demonstrated a multi-targeted Ru­(II)-Pt­(IV) conjugate that combines cancer-activated chemotherapy with photodynamic therapy with multi-action mechanisms to overcome drug-resistant cancers .…”
Section: Introductionmentioning
confidence: 99%